Mortality in takotsubo syndrome is similar to mortality in myocardial infarction — A report from the SWEDEHEART1 registry. (15th April 2015) - Redfors, Björn; Vedad, Ramtin; Angerås, Oskar; Råmunddal, Truls; Petursson, Petur; Haraldsson, Inger; Ali, Anwar; Dworeck, Christian; Odenstedt, Jacob; Ioaness, Dan; Libungan, Berglin; Shao, Yangzhen; et al.
Abstract: Background: Takotsubo syndrome is an acute cardiovascular condition that predominantly affects women. In this study, we compared patients with takotsubo syndrome and those with acute myocardial infarction with respect to patient characteristics, angiographic findings, and short- and long-term mortality. Methods: From the Swedish Coronary Angiography and Angioplasty Registry (SCAAR) and the Register of Information and Knowledge about Swedish Heart Intensive Care Admissions (RIKS-HIA), we obtained and merged data on patients undergoing coronary angiography in Västra Götaland County in western Sweden between January 2005 and May 2013. Short- and long-term mortality in patients with takotsubo ( n = 302) and patients with ST-elevation myocardial infarction (STEMI, n = 6595) and non-ST-elevation myocardial infarction (NSTEMI, n = 8207) were compared by modeling unadjusted and propensity score–adjusted logistic and Cox proportional-hazards regression. Results: The proportion of the patients diagnosed with takotsubo increased from 0.16% in 2005 to 2.2% in 2012 ( P < 0.05); 14% of these patients also had significant coronary artery disease. Cardiogenic shock developed more frequently in patients with takotsubo than NSTEMI (adjusted OR 3.08, 95% CI 1.80–5.28, P < 0.001). Thirty-day mortality was 4.1% and was comparable to STEMI and NSTEMI. The long-term risk of dying from takotsubo (median follow-up 25 months) was also comparable to NSTEMI (adjusted HR 1.01, 95% CI 0.70–1.46, P = 0.955) STEMI (adjusted HR 0.83, 95% CI 0.57–1.20, P = 0.328). Conclusions: The proportion of acute coronary syndromes attributed to takotsubo syndrome in Western Sweden has increased over the last decade. The prognosis of takotsubo syndrome is poor, with similar early and late mortality as STEMI and NSTEMI.